Septins: Regulators of Protein Stability - Vagin, Olga; Beenhouwer, David O. (Frontiers in Cell and Developmental Biology, 2016)
Septins are small GTPases that play a role in several important cellular processes. In this review, we focus on the roles of septins in protein stabilization. Septins may regulate protein stability by: 1) interacting with proteins involved in degradation pathways, 2) regulating the interaction between transmembrane proteins and cytoskeletal proteins, 3) affecting the mobility of transmembrane proteins in lipid bilayers, and 4) modulating the interaction of proteins with their adaptor or signaling proteins. In this context, we discuss the role of septins in protecting four different proteins from degradation. First we consider botulinum neurotoxin serotype A (BoNT/A) and the contribution of septins to its extraordinarily long intracellular persistence. Next, we discuss the role of septins in stabilizing the receptor tyrosine kinases EGFR and ErbB2. Finally, we consider the contribution of septins in protecting hypoxia-inducible factor 1α (HIF-1α) from degradation.